Rancang Bangun Mesin Pengupas Kulit Kacang Tanah Dengan Mata Pisau Berbentuk Spiral - Zaira, Jupri Yanda; Wijianto, Agus; Syahrizal; Taek, Oscar (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
The main purpose of making a peanut skin peeling machine is to meet the needs of peanut shelling when farmers are in the harvest season in peanut-producing areas. This machine is expected to help the stripping process, so as to increase production efficiency and quality. The stages of making a peanut skin peeler machine consist of needs analysis, preparation of product technical specifications, product concept design aims to produce alternative product concepts, after the product concept is obtained, the next step is product design which is product concept development in the form of sketches into technical objects, the last step in making this machine to make product documents in the form of working drawing designs. The specifications of the peanut skin peeler machine are with a capacity of 29 kg/hour, machine dimensions 1375 mm long x 648 mm wide x 1318 mm high. Using a driving force in the form of a 5.5 HP, 3600 rpm gasoline motor, the peanut skin peeler machine frame uses an L elbow profile of 40 x 40 x 40 mm. The peanut sheller machine transmission system consists of several components, namely pulley, v-belt, shaft, bearings, gearbox, and gasoline motor. The transmission system that we will make is using a gearbox with a gearbox ratio of 30: 1 and a pulley ratio of 1: 1. It will slow down the speed of a gasoline motorbike from 3600 rpm to 120 rpm. The mechanism that works on the transmission system starts from the gasoline motor which is transmitted to the gearbox shaft and from the gearbox shaft to the paring knife shaft using a v-belt will be transmitted, the connecting shaft uses a v-belt, at the same time the pulleys that have been attached to the v-belt on the connecting shaft are redistributed towards the pulley shaft of the paring knife using a v-belt which is used to rotate the paring knife to peel the skin of the peanuts.